EFL Students’ Hybrid Learning Experiences in Post-Pandemic Indonesia - Thedy Hardi Manafe; Sari Hidayati; Erica Ikramunnisa; Megi Sepriyanti Gobel (LPPM Universitas Advent Indonesia, 2026)
In Indonesia’s post-pandemic university context, where Hybrid Learning (HL) remains implemented in particular EFL Master’s courses, understanding how students experience and participate in a classroom that combines online and offline learning has become increasingly important. To explore EFL students’ overall experiences and participation in HL in a post-pandemic Indonesian context, focusing on how they perceived its strengths through their best experiences, how they perceived the challenges, and how they critically reflect on the challenges into suggestions for better implementation of HL. This study used a qualitative case study design with five EFL master’s students. Data were collected through semi-structured interviews and analyzed using Broun and Clarke’s thematic analysis. Member checking was conducted to ensure accuracy and credibility in capturing students’ HL experiences in the post-pandemic context. The findings showed that hybrid learning offered valuable flexibility and supported students with diverse backgrounds, allowing them to participate according to their needs and circumstances. However, they also faced challenges, particularly unstable internet connectivity and difficulty maintaining focus. To improve HL, students suggested stronger internet support, clear and balanced online-offline teaching, and more interactive teaching approaches. This study offers valuable insights into post-pandemic EFL education by showing that hybrid learning, when supported with improved infrastructure and thoughtful pedagogical design, can meaningfully enhance flexibility, learners' autonomy, and equitable participation for diverse student groups.